$\begin{array}{1 1}\sqrt 7.(\sqrt 3^n-1)(\sqrt 3+1) \\ \frac{\sqrt 7}{2}.(\sqrt 3^n-1)(\sqrt 3-1) \\\frac{\sqrt 7}{2}.(3^n-1) \\ \frac{\sqrt 7}{2}.(\sqrt 3^n-1)(\sqrt 3+1) \end{array} $

Want to ask us a question? Click here

Browse Questions

Ad |

0 votes

0 votes

- Sum of $n$ terms of a G.P.=$S_n=a.\large\frac{r^n-1}{r-1}$ where $a=$first term and $r=$ common ratio.

Given sequence is $\sqrt 7,\sqrt {21},3\sqrt 7........$

In this G.P. first term $=a=\sqrt 7$ and

common ratio$=\large\frac{\sqrt {21}}{\sqrt 7}=\frac{\sqrt 3\times\sqrt 7}{\sqrt 7}$$=\sqrt 3$

We know that the sum of $n$ terms of a G.P.$=S_n=a.\large\frac{r^n-1}{r-1}$

$\therefore$ Sum of $n$ terms of the given sequence $=\sqrt 7.\large\frac{\sqrt 3^n-1}{\sqrt 3-1}$

Rationalising the denominator we get

$S_n=\sqrt 7.\large\frac{\sqrt 3^n-1}{\sqrt 3-1}.\frac{\sqrt 3+1}{\sqrt 3+1}=\frac{\sqrt 7}{2}.$$(\sqrt 3^n-1)(\sqrt 3+1)$

Ask Question

Tag:MathPhyChemBioOther

Take Test

x

JEE MAIN, CBSE, NEET Mobile and Tablet App

The ultimate mobile app to help you crack your examinations

...